2003
DOI: 10.1034/j.1600-0455.2003.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Mr Imaging of Uncommon Recurrence of Fibrolipomatous Hamartoma of the Ulnar Nerve. A case report

Abstract: We present the MR and histopathologic findings of fibrolipomatous hamartoma (FLH) of the ulnar nerve in a 54-year-old woman, a lipomatous process that rarely affects the ulnar nerve. The case illustrated is further unusual as a local soft tissue recurrent mass developed over a remarkably long course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Most cases present with a longstanding painless mass. Nerve compression of the affected nerve with paresthesia, motor deficit and pain are known late symptoms [4,5,7,11-14]. It is suggested that it may become symptomatic only in the median nerve due to encroachment by the flexor retinaculum; thus causing carpal tunnel syndrome [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases present with a longstanding painless mass. Nerve compression of the affected nerve with paresthesia, motor deficit and pain are known late symptoms [4,5,7,11-14]. It is suggested that it may become symptomatic only in the median nerve due to encroachment by the flexor retinaculum; thus causing carpal tunnel syndrome [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…MDL has been given various names such as macrodactyly, megalodactyly, digital gigantism, macromelia, partial acromegaly, macrosomy, limited gigantism, fibrolipoma of nerve, fibrolipomatous hamartoma of nerve and lipomatosis of nerve, often described as having a ‘coaxial cable-like’ appearance on axial scans 5 6…”
Section: Discussionmentioning
confidence: 99%
“…According to few authors around 85% of cases show involvement of median nerve and its digital branches in hand, wrist and forearm. [2] It was Feriz in 1925 who first used the term Macrodystrophia lipomatosa for local gigantism of lower extremity. Bursky gave a more detailed description of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been given various names like, fibrolipoma of nerve, fibrolipomatous hamartoma of nerve and lipomatosis of nerve often described as having a ''coaxial cable-like'' appearance on axial scans. [2] It has also been described as megalodactyly, macrosomia and dactylomegaly.…”
Section: Introductionmentioning
confidence: 99%